2022
DOI: 10.1371/journal.pone.0270273
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lipid biosynthesis pathways for hepatitis B virus cure

Abstract: Chronic hepatitis B virus (HBV) infection is characterized by the presence of high circulating levels of non-infectious lipoprotein-like HBV surface antigen (HBsAg) particles thought to contribute to chronic immune dysfunction in patients. Lipid and metabolomic analysis of humanized livers from immunodeficient chimeric mice (uPA/SCID) revealed that HBV infection dysregulates several lipid metabolic pathways. Small molecule inhibitors of lipid biosynthetic pathway enzymes acetyl-CoA carboxylase (ACC), fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We found that silencing CTCF resulted in the upregulation of n =544 genes, which were associated with several pathways that are exploited by HBV. Fatty acid and bile acid metabolism are hepatocyte specific functions and represent the most significantly upregulated pathways and factors within these gene sets that are being actively explored as therapeutic targets for HBV cure (as reviewed in [52]). In contrast, the most significantly downregulated pathways were genes that are under the transcriptional control of Myc.…”
Section: Discussionmentioning
confidence: 99%
“…We found that silencing CTCF resulted in the upregulation of n =544 genes, which were associated with several pathways that are exploited by HBV. Fatty acid and bile acid metabolism are hepatocyte specific functions and represent the most significantly upregulated pathways and factors within these gene sets that are being actively explored as therapeutic targets for HBV cure (as reviewed in [52]). In contrast, the most significantly downregulated pathways were genes that are under the transcriptional control of Myc.…”
Section: Discussionmentioning
confidence: 99%
“…The exact contribution of immunity factors in the antiviral effect of these drugs needs to be further explored, and whether this general concept can be translated in vivo has to be determined. Lipid and cholesterol biosynthesis pathways are also considered as therapeutic targets in the treatment of HBV based on observations that drugs inhibiting these pathways decrease the production of subviral and/or viral particles ( 75 , 204 ). Interestingly, serum lipid profiles change in HCV-infected patients treated with direct-acting antivirals (DAA) and this correlates with viral clearance ( 205 , 206 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver-targeted ACC inhibitors effectively inhibit the secretion of hepatitis B surface antigens in HBV-infected HepG 2-NTCP cells. However, these inhibitors do not show antiviral activity in HBV-infected chimeric mice with humanized liver [186].…”
Section: Summary and Prospectmentioning
confidence: 94%
“…Liver-targeted ACC inhibitors effectively inhibit the secretion of hepatitis B surface antigens in HBV-infected HepG 2-NTCP cells. However, these inhibitors do not show antiviral activity in HBV-infected chimeric mice with humanized liver [186]. When ACC activity is inhibited in mice, lipids derived from the lipolysis pathway or diet may satisfy HBsAg production.…”
Section: Summary and Prospectmentioning
confidence: 99%